The geopolitical effect of the maritime factor on the spatial development of post-Soviet Russia: the Baltic case - Druzhinin A.G. (Baltic Region, 2023)
The article explores the impact of geopolitical processes on the spatial organisation of society, a matter that has gained increasing importance in Russia. It focuses on the utilization of the World Ocean and its coastlines for resource extraction, logistics, military-strategic purposes, and settlement. Methodologically, this study combines modern socio-geographical approaches emphasising the role of the maritime factor in spatial development with classical geopolitical ideologemes drawing a line between the land and the sea. It stresses the fundamental possibility for territories, including states, not only to acquire synthetic continental-maritime attributes but also to transform the balance of these attributes under the influence of geopolitical determinants. The article analyses geopolitically induced changes in the maritime activities pursued by Russia in the post-Soviet period. The primary focus is on the situational territorial and economic shifts of 2014 and 2022, and their implications for Russian territories in the Baltic region. Pronounced inter-basin differences are described with respect to the coastalisation of the population. The study also evaluates the economic condition of key Russian maritime centres and their resilience to external influences, especially geopolitical challenges. The article offers a geopolitical justification for Russia’s ongoing maritime endeavours, emphasizing the need for inter-basin, intermunicipal, and interregional integration. This integration should be accompanied by the establishment of coastal-intracontinental facilities, such as hubs, across Russia. It is imperative for the nation and its prominent corporations to actively engage in shaping the framework of emerging expansive international maritime socio-geographical structures, facilitating the shift toward global maritime polycentrism. The solution to these problems is closely linked to the priority goal of strengthening Russia’s geostrategic standing in the Baltic region, particularly with a focus on its maritime components. These developments are anticipated within the context of the Russian Baltic Area, envisioned as a borderland with trans-basin geopolitical, economic-geographical, and geocultural bi-structural asymmetry.